The best summer of our lives [large type] - Hauck, Rachel, 1960- (Thorndike Press large print Christian fiction series., 2023)
"Summer Wilde is a wannabe country music star. But when her latest girl band abandons her in a motel outside Tulsa, she is forced to face the shadows of her past. Twenty years ago, the summer of '77 was supposed to be the best summer of her life. She and her best friends, Spring, Autumn, and Snow--the Four Seasons, 4ever--had big plans. But those plans never had a chance. After a teenage prank gone awry, the Seasons found themselves on a bus to Tumbleweed, "Nowhere," Oklahoma, to spend eight weeks as camp counselors. Arriving with hidden secrets and buried fears, those two months changed their friendships and the course of their lives. Now, thirty-something and with no direction for her future, Summer is at a crossroads. Returning to the place where everything changed, she soon learns Tumbleweed is more than a town she left and never wanted to see again. It's the place for healing, for reconciling the past with the present, and for finally listening to love's voice. Celebrating the songs of our hearts, the joys of love, and the threads of friendship that tie us all together, New York Times bestselling author Rachel Hauck's radiant story perfectly captures all the romance, heartache, and hope of the best summer ever" --